STRATEGI KOMUNIKASI PEMASARAN PRODUK PRESSED MYLK MELALUI INSTAGRAM - Ni Putu Yunita Anggreswari; Ni Kadek Yosi Febrianti; Sulih Indra Dewi; I Putu Dharmawan Pradhana (Bajang Institute, 2024)
Abstract This study aims to determine the marketing communication strategy used by Pressed Mylk in marketing or promoting products to consumers through Instagram. By using qualitative descriptive research methods that aim to obtain in-depth, complete, and credible information and data so as to meet research objectives. This study also utilizes phenomenological methods to obtain maximum data and in accordance with the phenomena experienced by informants, in order to explain in detail the product marketing communication strategy carried out by Pressed Mylk through Instagram, using data collection techniques such as observation, documentation, and interviews to support the validation of research data. The result of this study is that Pressed Mylk has utilized Instagram features such as Instagram followers, Instagram bio, Instagram story, Instagram feed, Instagram reels, and story highlights to focus on introducing its products by uploading interesting photos or videos to attract consumers or buyers. Pressed Mylk uses 3 (three) communication strategies, namely push strategy, pull strategy, profile strategy and, Pressed Mylk applies an integrated marketing communication strategy that uses a marketing communication mix in the marketing communication strategy of Pressed Mylk products through Instagram such as advertising, sales promotion, event marketing, public relations, direct marketing, interactive marketing, and word of mouth well. From the results of this study, it can be concluded that Pressed Mylk has used Instagram well as a marketing communication medium for Pressed Mylk products, so that the effectiveness of using Instagram in marketing Pressed Mylk products has been proven through the sales turnover of Pressed Mylk products has increased